Utilization of Google Glassroom in Islamic Religious Education in Higher Education during the Covid 19 Pandemic - Sittika, Achmad Junaedi; Bintang Kejora, Muhamad Taufik (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
This study aims to obtain information and describe the planning, implementation and evaluation of Islamic religious education assisted by Google classroom media at Singaperbangsa Karawang University. The research was carried out using a qualitative descriptive method involving 87 students from 3 classes in the Computer Science Architecture Informatics Engineering Study Program. Data was collected through surveys, interviews, documentation, and observations. Data analysis was carried out using qualitative descriptive techniques and triangulation. The results showed that the use of the Google Classroom in Islamic Education learning was gradually able to improve the quality of learning. This is supported by good planning, competent teaching skills, systematic learning implementation, and measurable evaluation. The learning process is democratic, humanist and technological. Students are given initiative, innovation, freedom of creation so as to foster motivation, awareness, independence, and togetherness in learning. On the other hand, encouraging learning objectives by applying strict tuition contracts and strict sanctions for students who ignore the agreed upon learning. Online learning using Google classroom is able to improve the quality of teaching lecturers, interaction or student activity in learning, discipline, for timely assignments, the quantity of responsible students, student attendance in meetings through Google Meet, student interaction in learning and improving student learning outcomes. Despite the findings regarding positive benefits, the research revealed a serious social media complaint for some students.